The Effect Of Inflation Level And Bi-7 Day Repo Rate On Mudhrabah Deposits In Sharia Commercial Banks Period 2017-2019 - Siregar, Budi Gautama; Izzah, Nurul; Batubara, Damri; Sari, Novita (Journal of Islamic Financial Technology, 2022)
This research is motivated by the Inflation Rate and Bi-7 Day Repo Rate Against Mudharbah Deposits at Islamic Commercial Banks for the 2017-2019 Period. Total assets of Islamic banking reached 5.18% of total assets nationally, Indonesia was only able to rank 9th out of 10 other Islamic countries. This study aims to determine the effect of inflation rate and bi-7 day repo rate on mudhar bah deposits . Sharia Commercial Banks for the 2017-2019 Period. The method used in this study is quantitative, with the research location at Islamic Commercial Banks. The sampling in this study uses purposive sampling with a sample of 36 samples, the data analysis technique used is multiple regression analysis with t test to see the effect partially and f-test to see the effect simultaneously, assisted by using software SPSS 22.00. The results obtained in this study indicate that based on the partial test (t test) inflation does not have a significant effect on Mudhar bah deposits while the partial test (t test) and simultaneous test (F test) are inflation variables and Bi-7 Day Repo Rate has a significant effect on the Mudhar bah deposit variable at Islamic Commercial Banks 2017-2019.Keywords: Bi-7 Day Repo Rate , Mudharabah Deposits , Inflation